Evaluation of DLC, WC/C, and TiN Coatings on Martensitic Stainless Steel and Yttria-Stabilized Tetragonal Zirconia Polycrystal Substrates for Reusable Surgical Scalpels. (7th May 2013) - Pini, Stefano; Groppetti, Roberto; Mucchino, Claudio; Geretto, Valentina
Abstract : DLC, WC/C, and TiN coated SF 100 martensitic stainless steel and Yttria-Stabilized Tetragonal Zirconia Polycrystal (Y-TZP) surgical scalpels were tested, characterized, and comparatively evaluated with regard to chemical leach, micromorphology, and mechanical properties in order to evaluate their suitability as reusable surgical scalpels. Vickers microhardness (HV), Scratch Hardness Number (HS P ), and sharpening by grinding and cutting capabilities of all the coated scalpels were deemed appropriate for reusable surgical scalpels. However, coated Y-TZP scalpels demonstrated higher Vickers microhardness than martensitic stainless steel scalpels coated with the same coatings, except DLC coating on Y-TZP substrate that presented less adhesion than the other coatings. Uncoated and coated martensitic stainless steel scalpels presented corrosion and chemical leach when soaked for a defined period of time in a simulant physiological saline solution, while uncoated and coated Y-TZP scalpels did not present these drawbacks. Therefore, DLC, WC/C, and TiN coated SF 100 martensitic stainless steel surgical scalpels are unsuitable as reusable surgical scalpels, limiting their application to disposable scalpels only, as the uncoated ones, despite their higher microhardness and expected longer cutting capability duration. Based on these experimental results, WC/C and TiN coated Y-TZP scalpels can be proposed as candidates for reusable surgical scalpel applications.